Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 1881860415 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 1967-2022" ] } The dataset includes 1881860415 records from 31547 constituent datasets: 138 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 3 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 26 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 630 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 1127 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 6 records from Peliosanthes luteoviridis (Asparagaceae), a new species with yellowish green flowers from southern Vietnam. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 119 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 6 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 290 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2125 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 65 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 15758 records from University of Guam Insect Collection. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 87 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 400 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 5 records from Hydromedusae observed during night dives in the Gulf Stream. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 851 records from UWIZM Molluscs. 12 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 3960 records from MCP-Aves - Coleção de Aves. 135 records from Nannofossil abundance of Hole 36-329. 13 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 975 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 476 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 640 records from Bird specimens of Saitama Museum of Natural History. 1 records from Vascular Plants of Murmansk Region at the Komarov Botanical Institute (LE), St. Petersburg, Russia. 118 records from orthopteracollections-nhmj-ioj. 1 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10756 records from Collections of Bioclass, school #179, Moscow. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from Dinoflagellate abundance of Hole 14-144. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 12 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 253994 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 36 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 240 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1150 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 18 records from Naturtag. 17588 records from Herbier Louis-Marie (QFA) - Collection de lichens. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BLANC Josselyne. 912 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 251 records from Monitoring of colonial waterfowl species (2013-2014). 142 records from Colección de Zoología Universidad Icesi: Mamíferos. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 21 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 760 records from Total foraminifera counts of multinet M21/2_MSN650. 6739 records from Colecção Entomológica IIA. 16614 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 1211 records from Wintering wildfowl in Portugal – 1992-1993. 1188 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 3770 records from Spatial and temporal ichthyofauna community of a tropical mangrove Bay (Gazi Bay, Kenya) sampled between 1994 and 1996. 77 records from DMNS Egg Collection (Arctos). 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 16 records from Insect Collections of Okomu National Park- Nigeria. 260447 records from ARABEL - Arachnologia Belgica. 92959 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1005 records from Missisquoi National Wildlife Refuge Bumblebee (Bombus) Surveys. 61 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 245 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 655 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 85 records from Projet de transport par câble entre le Chaudron, Moufia et Bois de Nèfles - Oiseaux - inventaires. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 42 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1902 records from Midden-Limburg Fish Ponds Survey. 162 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 50169 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1803 records from AMAPPS Northeast Aerial Cruise Summer 2016. 529 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Geometridae de France métropolitaine. 17 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 817 records from Sampling event dataset of Shasha Forest Reserve, Osun State, Nigeria. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 10750 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 23979 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 7412 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2018. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 8004 records from Inventario de Hymenóptera; parasítica en México. 551 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 2 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Oiseaux. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 61 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 63 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 26518 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 70 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LE GLOANEC Vincent. 190232 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81, 1983-5. 204 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 280 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 657 records from Whale catches in the Southern Ocean. 21 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 230 records from Biometría peces Parque Nacional Natural La Paya. 50 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9281 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 1 records from Polystichum jinpingense (subg. Haplopolystichum; Dryopteridaceae), a new fern from southeastern Yunnan, China. 21 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 950 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 147 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 1668726 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 4605 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 706 records from South American Antarctic Marine Biodiversity Literature. 13810 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 48 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 84 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from California State University, Long Beach Birds. 1164 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 407 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 2699 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 48 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1787 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 48 records from Regroupement d'études et inventaires - Données opportunistes sur les odonates. 348 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 11672 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2018. 174 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 321 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1409 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 912 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 345 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire entomologique 2020 de la réserve biologique dirigée du Nord Grande Terre, Guadeloupe (ONF). 16743 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 3 records from On a collection of Scaphisomatini (Coleoptera: Staphylinidae: Scaphidiinae) from West Malaysia. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 34 records from Happywhale - Bryde's whale in South Atlantic Ocean. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 108 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 529 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 29 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 4820 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 2280 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 83932 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 84532 records from Fish specimens of Kagoshima University Museum. 3583 records from UTEP Invertebrates (Arctos). 1316 records from Fish occurrence in Kuban River basin. 312 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 6 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 1875 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 882 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 20 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 899 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 20 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 5 records from Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 90 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 870857 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 412243 records from DATAVES. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 6 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 700 records from Distribution of nanoplankton at trap WR2. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 260 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 141798 records from Fermanagh Flora. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 31 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 15 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 16 records from Revision of the Oriental genus Horniella Raffray (Coleoptera, Staphylinidae, Pselaphinae). 448 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 2 records from A new species of crown-antlered deer Stephanocemas (Artiodactyla, Cervidae) from the middle Miocene of Qaidam Basin, northern Tibetan Plateau, China, and a preliminary evaluation of its phylogeny. 81 records from Kystfuruskoger i Tysnes og Fusa. 1 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 79 records from Diatom abundance of Hole 95-613. 1562 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 207 records from Inventaires et suivis faune - Inventaire et suivi des libellules – Protocole STELI. 8 records from Die Bachspezies 2008/2009. 61 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 3413 records from Réseau de suivi des macro-invertébrés aquatiques - Inventaire et suivi Macroinvertébrés. 72 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 1275 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 371 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from On the taxonomy of Negeta semialba Hampson, 1918 with descriptions of two new Leucobaeta László, Ronkay & Witt, 2010 species (Lepidoptera, Nolidae, Nolinae). 2332113 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 10 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 1 records from A clarification of B. C. Seeman’s Malagasy species of Colea Meisn. (Bignoniaceae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 3010 records from Inventaire de la flore de la Vienne 2009-2018 - Inventaire de la flore du Grand Poitiers 2009. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier DELZONS. 141 records from Naturalis Biodiversity Center (NL) - Diptera. 207 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 106 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 5985 records from Distribution of foraminifera of sediment core GIK23258-2. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 3 records from First description of the metopiine genus Trieces Townes, 1946 (Hymenoptera: Ichneumonidae) from the Indomalayan region with three new species from India. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Majidae crabs from Morrocoy National Park - Venezuela. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 1 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 4 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 44219 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 10 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Chauves-souris - Points d'écoute au sol. 4117 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 16 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 256 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 392 records from Hawthorne Canal Birdwatching Survey. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 210 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 232 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 5810 records from Grassland cartography SICONA, Recorder-Lux database. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 14 records from A new species of Pristimantis Jiménez de la Espada, 1870 (Anura: Strabomantidae) from the “ Brejos de Altitude ” in Northeast Brazil. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 24 records from Analyses of the recent components of sediment core PS1011-1. 21 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from Verbascum birjandense and V. urumiense (Scrophulariaceae), two new endemic species for Flora of Iran. 30 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 6 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 6 records from Foraminifera abundance of Hole 58-442. 1668 records from Banco de semillas Jardín botánico de Cartagena "Guillermo Piñeres". 13 records from Coleção de Coleoptera da Universidade de Brasília. 45 records from Natterjack Toads of Ireland. 98 records from Warnowtal (Rostock). 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 386063 records from Compost microbe establishment and growth in agricultural soils. 13 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202114 records from National Benthic Inventory. 6 records from Plan de gestion 2016 - 2020 du site du domaine de Rodié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 16 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 286 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 236673 records from Kastikka Floristic Archives (KEVO). 1332 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1184 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 199 records from Demospongias de la Laguna La Restinga, Venezuela. 167195 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 380693 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 840 records from Collection Trichoptera - SMF. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 73 records from Projet éolien - Insectes - Inventaire non protocolé. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 99 records from Planktic foraminifera abundance of Hole 27-262. 3822 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 27 records from Planktic foraminifera abundance of Hole 27-260. 81674 records from Arizona State University Hasbrouck Insect Collection. 224 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3352 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 34 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1369 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 87901 records from MDFRC macroinvertebrate survey. 64 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des reptiles 2014. 35 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 10 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 11934 records from Inventaire de la flore de Charente-Maritime 2012-2020 - Inventaire de la flore de Charente-Maritime 2017. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 5253 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 61 records from Shrews of Poland. 8 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 9 records from Nannofossil abundance of Hole 2-11. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 4349 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 4 records from Two new species of Begonia (section Petermannia, Begoniaceae) from the Zamboanga Peninsula, Philippines, and a redescription of Begonia parvilimba. 1036 records from BUND - Dassower See (Lübeck/Dassow). 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 43249 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur François FOURNIER. 53796 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 279 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 2820 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 39 records from Planktic foraminifera abundance of Hole 14-137. 784 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 1287 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur JOURDE Rémi. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 60 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 26327 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 2560 records from Upper Silesian Museum, Bird Observations. 142 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 28 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1127 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 259 records from SEWBReC Springtails and allies (South East Wales). 368 records from Benthic foraminifera abundance in ODP Leg 155 holes. 85205 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 306 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 330 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 106 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 164 records from Ladybirds of Ireland. 13 records from Collections ichtyologiques et herpétologiques (BOUM). 15011 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6175 records from NE Scotland fish records 1800-2010. 144 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 58372 records from Fichier communal des ongulés. 809 records from Especies vegetales asociadas a intervenciones de micrositios en la Reserva Forestal Thomas van der Hammen. 43 records from Projet éolien de Saint-Barbant - Autre faune. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 12 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 6300 records from Service National d'Observation CORAIL - Réseau de surveillance Polynesia Mana - Peuplements de poissons. 32 records from Living Cirripedia. 3551 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 5 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 218 records from Land and freshwater molluscs of Northern Spain. 23 records from Novitates neocaledonicae. IX. Taxonomic notes on New Caledonian Diospyros (Ebenaceae) with new synonymy and the description of two new species. 2407 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 760 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 3949 records from University of Nebraska State Museum Birds Collection. 25621 records from University of California Santa Barbara Invertebrate Zoology Collection. 319 records from Seasonal variation of the zooplankton community at Gazi, Lamu and Malindi (Kenya) sampled between 1990 and 1992. 232 records from Planktic foraminifera abundance of Hole 21-207. 110 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 8 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 10729 records from WOLL AVH data. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 3 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 29 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 1140 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 1 records from Anemone pindariensis (Ranunculaceae), most recently described from the western Himalaya in India, is a teratological form of A. rivularis. 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 5 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Yves BOUTET. 1845 records from Données des collections du MNHN - Données des collections d'algues du MNHN. 2140 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 74 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 2159 records from Données Association Évasion tropicale (AET) - Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 199 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne d’investigations ichtyofaune – Ferme pilote de Groix & Belle-Ile. 106 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 189 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 950 records from Total foraminifera counts of multinet M21/4_MSN694. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 4 records from Two new species in the Russula (Russulaceae, Basidiomycota) crown clade from Indian Himalaya. 46 records from An der Ohm, (Wettsaasen). 88 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 97 records from Elaboration du DOCOB du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire des odonates d'intérêt communautaire. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 12 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 800 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 377 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 444 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1804 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 69 records from Jurica-Suchy Nature Museum at Benedictine University Fossil Specimens (Arctos). 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 1520 records from Total foraminifera counts of multinet M21/6_MSN784. 49 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 40 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 22764 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 608 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 76 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 10 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 4556 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 576 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 829 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Grand Voyeux - Suivis scientifiques. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 37 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 75 records from UWIZM Cnidarians. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 243 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 63 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 167016 records from Tasmanian Museum and Art Gallery provider for OZCAM. 860 records from TTRS Mammals. 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 2247 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 151 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 526 records from Eventos de monitoreo de la especie plaga Didymosphenia geminata en cuerpos de agua de la zona centro sur austral de Chile, Etapa I (2016 - 2017). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 1 records from Discovery of a new species of Euphlyctis (Anura: Dicroglossidae) from the western coastal plains of peninsular India. 92312 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 4 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 17727 records from Chrysomelidae beetle data from iRecord. 60 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 64903 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 120 records from Faunal assemblage of sediment core TR149-32. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3 records from Novelties in Phyllanthus (Phyllanthaceae) from the Brazilian Cerrado: new records of the rare species P. allemii. 125 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 360 records from Planktic foraminifera counts at CTD station PS55/079-1. 1 records from First record of the freshwater crab genus Esanthelphusa Naiyanetr, 1994 (Decapoda: Brachyura: Gecarcinucidae) from Myanmar, with the description of a new species from the Kayin State. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1411 records from La familia Asclepiadaceae en México. 2 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 2 records from Revalidation and redescription of a gobionine species Microphysogobio bicolor (Nichols, 1930) (Teleostei: Cypriniformes) from the Yangtze River Basin, China. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 370 records from Otter survey of Ireland 2004 & 2005. 1054 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 120 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 155 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1556 records from Happywhale - Gray Whale in North Pacific Ocean. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 87612 records from Suivi Temporel des Rhopalocères de France (STERF). 8 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 2 records from Zapada (Plecoptera: Nemouridae), a stonefly genus new to the fauna of China. 2485 records from Study of epifauna and meiobenthos by means of cage experiments in a Ceriops tagal and Avicennia marina mangrove at Gazi Bay (Kenya) in August and September 1992. 312 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 4 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 75 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 2016 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 76 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 245 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de VINCENT Alexis (SAPROX). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 3 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 74 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 218 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 9 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 1 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 8 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 11387 records from 16S data from: Diversity of Pico- to Mesoplankton along the 2000 km Salinity Gradient of the Baltic Sea (Hu et al. 2016). 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 6652 records from Inventory of plant species through Benin (West Africa). 6032 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 245 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 11 records from Two new species of Colea Bojer ex Meisn. (Bignoniaceae) endemic to Madagascar. 293 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1702 records from BioGIS - Bryophytes - HUJ collections. 742 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1384 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 2208 records from marine sediment metagenome Raw sequence reads. 2 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 235 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 164 records from Harpacticoid copepods in tropical seagrass beds of Gazi Bay (Kenya) and Mbweni (Zanzibar) sampled in July and August 1996. 47 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 371 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 270 records from 59 - Beau Gui Avifaune. 120 records from BIRDRACE The early birds. 1714 records from Regroupement d'études et d'inventaires - Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 122 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 51 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 44 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Amphibien - POPAmphibien. 16 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 3795 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 21 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 2011 records from UNCW Right Whale Aerial Surveys 2008. 728 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 3120 records from Pollen record of sediment core Bokanjacko Blato 1. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 59 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 480 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 516 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 76 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement de la commune de Chepnier. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 24424 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 38 records from Happywhale - Crabeater Seal in Southern Ocean. 589 records from Planktic foraminifera distribution of sediment core SU81-07. 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 33 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 204 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 179 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 124463 records from Herbarium of Taiwan Forestry Research Institute. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 791 records from Inventaire Odonates-Rhopalocères 1999-2002 du PNRLG - Données odonates. 231 records from Malawi-Histeridae-Biodiversity-Data. 426 records from Planktic foraminifera abundance of Hole 7-64. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 333 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Flore - Inventaire non standardisé - FRAPNA74 - 24HNAT. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 1 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 200 records from Plantas de la Ecoreserva Campo Rubiales (Meta, Puerto Gaitán) - Proyecto FIBRAS. 23830 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1140 records from Total foraminifera counts of multinet M21/1_MSN608. 24 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 3700 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 3058 records from Données Association Évasion tropicale (AET) - Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 704 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 1818 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Anaïs MAS. 1073 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 7 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 6 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 47 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Abundance of benthos infauna at station GIK23065-1. 17771 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 300 records from Flux data of NU2_trap (Table A1). 2834443 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 227 records from Bishop's University Insect Collection (BUIC). 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 5346 records from Sediment metagenome. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 29 records from Happywhale - Blue Whale in Southern Ocean. 11242 records from Happywhale - Humpback Whale in North Atlantic Ocean. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 2151 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 673 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 150 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 24 records from Plan de gestion 2007 - 2011 du site du Coteau de Peyroutet (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 68 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 32 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 171 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 91 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 31 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 24 records from Caracterización de Mamíferos en el área de Farallones, jurisdicción de CORPOGUAVIO. 385 records from Eufáusidos norte de Chile. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 196624 records from Kastikka Literature Sources. 12 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 2690 records from Gymnasium students as bat researchers. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 361 records from Nannofossil abundance of Hole 66-490. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1598 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 5874 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 38 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 14 records from Contribution à la connaissance des Orthoptères – Locusta - Données opportunistes de Benoit DUHAZE. 912 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2490 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Alain BERLY. 26110 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 1 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 500 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 238 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 8318 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 70 records from PARC PHOTOVOLTAIQUE à RIANS - Flore. 451130 records from Inventaire de la flore d'Alsace - Données de la flore d’Alsace (SBA). 1248 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 307 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 450 records from 2020_nsmk_smpl_sw_450. 16788 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 2 records from Suivi Cistude d'Europe du Bassin de stockage de Balanos - Données Cistude d'Europe du Bassin de stockage de Balanos. 168 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 98658 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 1598 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 879859 records from Flore Franco-Belge. 16954 records from EAC - Herbário Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1519 records from Leif Richardson Vermont Bee Specimens. 5 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 4 records from Plan Aquitain d'Action Sonneur à ventre jaune - PRA Sonneur à ventre jaune - étude de répartition. 3744 records from Collection Crustacea - ZMB. 47 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Suivi Amphibiens dans le cadre du chantier. 644 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 4 records from Le genre Oxyanthus DC. (Rubiaceae) en Afrique de l’Ouest: description d’une nouvelle espèce. 710 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 1 records from Parc éolien d'Argillières - hérpétofaune. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 200 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 1140 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 30 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 8932 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 156 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 13 records from Warnowufer Groß Klein. 109 records from Planktic foraminifera abundance of Hole 18-181. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 6219 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1280 records from University of Central Arkansas Herbarium. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 46 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 13 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 47 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 11 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LESSIEUR David. 23216 records from Species inventories NP Öewersauer, Recorder-Lux Database. 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 68 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - FRAPNA74 - 24HNAT. 416 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 825 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24469 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 3040 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 8336 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 553 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 20 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 10825 records from Census of species recorded during phytosociological surveys in Benin. 6235 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 352 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 313 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 7579 records from Collection Pisces SMF. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41139 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 57 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 32935 records from Botanical Museum, Copenhagen, Mycology Herbarium. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 8402 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 3 records from Mise en oeuvre des mesures compensatoires à l'aménagement du parc photovoltaïque d'Hourtin - Données opportunistes. 19 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 2025 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 89951 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 206794 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 4 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 9 records from tranfert des activités ferrovaires du site de Nantes-Etat vers le site de Nantes-Blottereau - Inventaire d’espèces végétales protégés et/ou patrimoniales - Point. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 507 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations d'odonates réalisées lors de journées de prospections animées par la LPO Aquitaine. 134 records from CHAS Botany Collection (Arctos). 1140 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 18 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 4851 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 33 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 213 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 6303 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Marc GAGNE. 16505 records from Database for alien invasive plants occurrences in Germany. 60 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 69 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par la Réserve naturelle nationale de l'Étang Noir selon le protocole STELI adapté pour le programme. 1332 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 115 records from Strathclyde badger sett surveys 1996-2000. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 4377 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 319 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 2115 records from Atlas des papillons de jour et des libellules du Languedoc-Roussillon - Données CEN L-R papillons/libellule. 12380 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 2 records from A new species of Pristimantis (Anura: Strabomantidae) with a colourful venter from the cloud forests of Colombian western Andes. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 560 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 81 records from Parc éolien du Mont de Bagny II - Inventaire de la flore sur l'aire d'étude. 2326 records from Inventaire des Mollusques Sphaeriidae de France. 11094 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CORNIC Jean-François. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 2817 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 614 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3318 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 372 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 75 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 83972 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 210 records from Pollen profile II/B at Krumbach, Germany. 24422 records from Weevil and Bark Beetle records via iRecord. 24 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 66 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 51 records from Stigmella stettinensis (Nepticulidae) specimen data. 640 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 33 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 17 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama. 8158 records from Dark ocean microbial diversity. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 443 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 3320 records from BioGIS - Mammals - SPNI. 569 records from Amphibia and Reptilia (Luomus). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 84 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 174 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 7603 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 912 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 1 records from Review of the genus Mesosaimia Breuning with description of a new species (Coleoptera: Cerambycidae: Lamiinae: Mesosini). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 1592 records from MEXU/Flora de Oaxaca. 30791 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 7 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 2 records from Two new freshwater species of Bacillaria (Bacillariophyta) from Dongting Lake, China. 58313 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 6248 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 147 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 39965047 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 117 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 33 records from Bohemannia auriciliella (Nepticulidae) specimen data. 13 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 74 records from Nannofossil abundance of Hole 39-359. 24 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4105 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 112 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 34 records from Abundance of benthos infauna at station PS1240-1. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 1079 records from Mediterranean seabird surveys 99/00/02. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 611 records from Données du Parc National de la Guadeloupe - Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 605 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CARR David. 1262 records from Regroupement d'études et inventaires - Collecte données faune Simethis 2014-2019. 4 records from Nannofossil abundance of Hole 3-22. 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 132 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 91 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 138 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de GERBAUD Joël. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 88 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 900 records from Collembola of forest tundra ecosystems of the Sula (Malozemelskaya tundra) and Bolshaya Rogovaya (Bolshezemelskaya tundra) rivers. 21421 records from JCT AVH data. 68 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 2244 records from Amphibiens de Guyane. 134 records from Nannofossil abundance of Hole 7-62A. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Nannofossil abundance of Hole 9-82. 8 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 50 records from Happywhale - Fin Whale in South Atlantic Ocean. 1 records from Efecto anti-proliferativo del extracto hexánico de las hojas de Hymenaea courbaril L. (algarrobo) y su relación con la inducción de apoptosis en células de cáncer de próstata pc-3. 4 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 77969 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 2 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3223 records from Dorset SW Pilot species dataset. 1830 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - ex région M-P. 68 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 448 records from Benthic macrofauna abundance of sediment core 13077-087. 144 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Odonate - STELI. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 61 records from Regroupement d'études et inventaires - Inventaire et suivi de la faune écrasée. 1000 records from nsmk_mm_2019. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 16289 records from Vegetation of the Rybachy Peninsula and the Sredny Peninsula, Murmansk Oblast, Russia. 5800 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 450 records from 2020_nsmk_smpl_pl_450. 1824 records from Diatom assamblage in samples from sediment trap OG4. 381 records from DAR AVH data. 11 records from Happywhale - Commerson's Dolphin in South Atlantic Ocean. 13 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 170529 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 609 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 3132 records from Ross A. Layberry, Collection. 3 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 739 records from IOV Fitoplancton del Saco del Golfo de Cariaco, Venezuela. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 92 records from Microfossil abundance of Hole 50-416A. 30 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 10 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 122 records from Avifauna asociada a la parcela de investigación de la estación Tutunendo, Quibdó, Chocó. 2020. 1 records from DRYMONIA MEXICANA (GESNERIACEAE), A NEW ENDEMIC SPECIES FROM VERACRUZ (MEXICO) Laura Clavijo. 100 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 408 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 17 records from North Carolina Rehabilitated Sea Turtle Monitoring Project (aggregated per 1-degree cell). 3274 records from Colecção Entomológica do Museu de História Natural de Maputo. 91 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 1 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 8293 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 1140 records from Total foraminifera counts from M35/1_MSN1051. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 231 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 3807 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 5 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 284235 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 243 records from Thistles species and abundance. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2062 records from Flora vascular acuática de la cuenca del Río Tamesí. 716 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 2177 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Mares. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 9 records from Type locality records of Polycystididae species in the world. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 711 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Stéphane ORIO. 339 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3868 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 609 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 7 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 61 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from Projet d’élargissement à 2x3 voies de l’autoroute A4 sur le Contournement Nord-Est de Metz (CNEM) - Zones de présence d'espèces animales et végétales. 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 107 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 150 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 272 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 5 records from Molecular analysis of five controversial Balkanic species of Allolobophora (sensu lato) Eisen, 1873 (Lumbricidae, Clitellata) with emendation of the genus Cernosvitovia Omodeo, 1956. 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 2180 records from Jardín Botánico Atlántico, Gijón/Xixón: Herbarium JBAG. 11 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 3128 records from Regroupement d'études et d'inventaires - Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 302 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 28 records from Données sur les Opisthobranches et Planaires de Mayotte. 2539 records from Waterbird counts, Luomus dataset. 308 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 132 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 106 records from Planktic foraminifera abundance of Hole 94-611. 70 records from Abundance of zooplankton in the Aral Sea. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 2592 records from Phytoplankton abundance in surface water during cruise CD61. 228 records from Total foraminifera counts of trap L3_92_45. 43 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 107 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 722 records from Heritage Trees of Ireland. 48 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 573 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 2742 records from McDonald-Podesta-Fortuin-Gandhi Orchid Bee Collection. 95 records from Elaboration des DOCOB des sites Natura 2000 ‘Plateau d’Argentine’ (FR7200810) en 2009 et ‘Réseau hydrographique de la haute-Dronne’ (FR7200809) en 2010 - Inventaire et suivi Entomologique de Desmond KIME. 371 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 108 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 41186 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 8 records from RISC Non-Native Species Records for Zebra Mussel. 139 records from Nannofossil abundance of Hole 55-433. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 1276 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 5961 records from Zooplankton studies in the Southern Bight of the North Sea between 1971 and 1974. 59 records from Cayman Islands 2004: Loggerhead & Green Turtles (aggregated per 1-degree cell). 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 14 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 57 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 321 records from Freshwater fish records via iRecord - additional species. 98 records from Abundance of benthos infauna at station GIK23055-1. 9 records from A new species of Anchoviella Fowler, 1911 (Clupeiformes: Engraulidae) from the Amazon basin, Brazil. 330 records from Benthic macrofauna abundance of sediment core 13200-017. 490 records from Ixias butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 4532 records from Gunma Museum of Natural History, Fungi Specimen. 1 records from Juvenile loggerhead use of the Gulf Stream off Cape Hatteras, NC (aggregated per 1-degree cell). 12558 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 3 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 7 records from Typhloplanoida from the southern hemisphere (Zanzibar, Kenya, Kerguelen, Australia and Weddell Sea). 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 13 records from Scorpions of the Horn of Africa (Arachnida, Scorpiones). Part XIV. Hottentotta somalicus sp. n. (Buthidae) from Somalia. 1 records from Plan de gestion 2016 - 2020 du site du Coteau de Savoye (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 208350 records from PIROP Northwest Atlantic 1965-1992. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 8 records from Cryptic new species of Nesoecia Scudder, 1893 (Orthoptera: Tettigoniidae Pseudophyllinae) from northeastern, Mexico. 153 records from Happywhale - Southern Right Whale in South Atlantic Ocean. 1650 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 62 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée de 2013 à 2017. 125 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 152570 records from UWFC Ichthyology Collection. 2 records from A revision of pipistrelle-like bats (Mammalia: Chiroptera: Vespertilionidae) in East Africa with the description of new genera and species. 84 records from Etude d'aménagement foncier lié à la desserte du CHNDS - Inventaire de Lépidoptères et des Odonates. 38 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 3698 records from Mycological Collection of Osaka Museum of Natural History. 82 records from UNCW JAX Aerial Survey - Right side - 2016. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 23 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 7 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 48 records from Animation du site Natura 2000 ‘La Vallée de l'Avance’ (FR7200739) - Données opportunistes. 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 735 records from EDP Foz-Tua: Vascular Flora – Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 17 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 307 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 26084 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 2248 records from MUST, Insecta. 12 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Déplacement d'amphibiens dans le cadre du chantier. 68 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 855652 records from Données ONF faune-flore-fonge. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 70 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 992 records from Regroupement d'études et d'inventaires - Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 17 records from Notice de gestion 2019 - 2023 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 2 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 2362 records from University of Michigan Museum of Zoology, Division of Mollusks. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 32 records from Site Condition Monitoring of the downy willow Salix lapponum component of the Vascular Plant Assemblage interest of Skinsdale Peatlands SSSI, 2016. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 126 records from Range table from benthic foraminifers in ODP Hole 144-874B. 24334 records from Données acquises par le Conservatoire botanique national du Bassin parisien et son réseau (bénévoles, associations, autres structures professionnelles) - Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 57660 records from DASSH Data Archive Centre Academic Surveys. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 30 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 1129 records from SWFSC Marine Mammal Survey, CalCurCEAS 2014, Cruise 1647. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 6187 records from Study of specific plant diversity in forest reserves and riparian areas in Benin (Part 2). 556 records from Expedición ornitológica en el municipio de Barbacoas (Nariño) - BIO Alas, cantos y colores. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 131 records from Mariposas diurnas presentes en los parques urbanos de Bogotá. 85 records from The ant genus Strumigenys Smith, 1860 (Hymenoptera: Formicidae) in western North America North of Mexico. 24 records from Composición florística y anatómica de plantas acuáticas en caños negros (humedal Coroncoro-Villavicencio) en temporada seca y lluviosa, departamento del Meta. 189507 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 30 records from Observations naturalistes de la réserve naturelle nationale des prés salés d'Arès et de Lège-Cap Ferret - Plan de gestion 2016-2020 - Inventaire et suivi Faune - Protocole Wetlands International. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Thibault RAMAGE. 7 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 43 records from Vogelstimmenführung durch den Tiergarten. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 933 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin de la Société Linnéenne de Bordeaux. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 2975 records from Tetrápodos de Uruguay. 50 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 315 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 1840 records from Swiss Psyllid (Hemiptera) Collections - Basel. 61 records from Virginia CZM Wind Energy Area Survey- Vessel Survey Sightings - November 2012 through April 2014. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 1 records from Two new species of the genus Bolboceras Kirby, 1819 (Coleoptera: Bolboceratidae Bolboceratinae) from India with an updated identification key of the Bolboceras nigricans Westwood, 1848 species group. 15 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 2210 records from Overvåking av dragehode Dracocephalum ruyschiana. 338 records from Planktic foraminifera abundance of Hole 15-148. 30900 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 1 records from Timaviella dunensis sp. nov. from sand dunes of the Baltic Sea, Germany, and emendation of Timaviella edaphica (Elenkin) O. M. Vynogr. & Mikhailyuk (Synechococcales, Cyanobacteria) based on an integrative approach. 3528 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 278 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - données bibliographiques diverses (non araignées). 3 records from Riegeriana, a new genus for Physopelta apicalis, and checklist of the genus Iphita (Hemiptera: Heteroptera: Largidae) with description of one new species. 7 records from Small, uniform, and rarely collected-an integrated taxonomic revision of Afromicracis bark beetles (Coleoptera, Scolytinae). 1518 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 22 records from New records of ant species from Yunnan, China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 5 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 763 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 35 records from Macrofaunal composition and zonation on sandy beaches at Gazi, Kanamai and Malindi Bay Kenya between April and December 1986. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 12 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2299 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 122 records from SILENE-FAUNE-PACA - BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 16 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 433 records from Envoi de données complémentaires disponibles à la SFEPM pour l'atlas des Mammifères de France - Données Loutre compilées par la SFEPM pour compléter les cartes de l'atlas national des Mammifères.. 1763 records from Arachnida of Costa Rica (INBio). 2 records from Solanum coalitum (Solanaceae), a New Endemic Species from Southern Ecuador. 3 records from New austral-most records of the genus Heterostylum Macquart (Diptera Bombyiliidae) in Argentina. 8 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 432 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 95 records from Nannofossil abundance of Hole 22-217. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 900 records from 2020_nsmk_smpl_in_900. 912 records from Total foraminifera counts of multinet M21/5_MSN728. 2 records from Projet de parc solaire Figanieres - Mammifères - Inventaire non protocolé. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 85 records from Données espèces - Expertise IPE 123. 60 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 50 records from Beetles on polypores at 4 sites in Norway. 1224 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 1704 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 89 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 1 records from 1ère phase d'animation (2010 - 2018) du Document d’objectifs du site Natura 2000 FR7200669 - Vallon de la Sandonie (24) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 75 records from Projet artère de l'Adour réalisé par ECOSPHERE - Inventaire et suivi Rhopalocères. 1044 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 3185 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 157 records from BIRDRACE Rheinische Wasserrallen. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Pakistan. 16 records from New records of Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from India. 3723 records from Abundance and biomass of zooplankton collected in front of the Danube Delta in May and September 1979. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 3 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 1144 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 4388 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de David HAPPE. 5 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 5346 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 912 records from Total foraminifera counts from multinet M31/2_MSN890. 3082 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 932 records from CNAN/Araneae. 42 records from Estimated plankton abundance at station PS63/064-6. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 29 records from New apinnate Prionospio (Annelida: Spionidae) species from southeastern Brazil. 71 records from Evaluación de la diversidad biológica y las relaciones tróficas de las charcas estacionales del norte de La Guajira. 240 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 840 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 111 records from Liste commentée des Saturniidae (Lepidoptera, Bombycoidea) de Guyane, avec la liste des taxons récoltés au Mitaraka (extrême sud-ouest guyanais). 3185 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 4 records from Animation des 4 sites Natura 2000 des zones humides du Marensin - Inventaire et suivi de la Cistude d’Europe sur le site Natura 2000 ‘Zones humides de Moliets, La Prade et Moisans’ (FR7200718). 9 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 89 records from Colección de Zoología Invertebrados - Helmintología. 36 records from Early Land Plants Today: Index of Liverworts & Hornworts 2013 - 2014. 28 records from Anfibios de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 2 records from A new species of the “ apacheanus ” group of genus Pseudouroctonus from western Texas (Scorpiones: Vaejovidae). 89 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 912 records from Total foraminifera counts of multinet POS247/2_MSN1384. 27509 records from Fishes of INEP and NFH collections. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 46 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 180 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 54 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 118 records from Plan de gestion 2016 - 2020 du site du coteau de Pinel (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 31 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Planktic foraminifera abundance of Hole 19-185. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 11 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 14 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 2 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 2776 records from Biodiversity of the Desna river valley and its tributaries. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 50 records from Reptiles de la Ecoreserva ASA (Meta, Acacías) - Proyecto FIBRAS. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 5 records from Loricifera - SMF. 96 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 478717 records from KTP Ring Data. 88 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 580 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 2 records from Brown University Herbarium. 44 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 11187 records from Inventaire de la flore des Pyrénées-Atlantiques (hors massif pyrénéen) - Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 21 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 133176 records from Happywhale - Humpback Whale in North Pacific Ocean. 9 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" site de La Beute (Tosse). 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 36 records from The genus Hybos em> Meigen (Diptera: Empidoidea: Hybotidae) in Thailand strong> p>. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 8799 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 69 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 59 records from Schulgelände SGD/Viersen. 943 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 1281 records from Flora genérica de las gramíneas del estado de Tlaxcala. 57 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 4 records from Colección Palinológica del Herbario LIL (PAL-TUC-FML-Tucumán). 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 399 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 5661 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 365 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 4 records from Schistura thavonei, a new species of loach from northwestern Laos (Teleostei: Nemacheilidae). 75 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 6436 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 8 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Propriété régionale du Moulin des Marais - Inventaire naturaliste 2015. 37 records from Two new species of Petalophthalmus and Ipirophthalmus (Crustacea: Mysida: Petalophthalmidae), from New Zealand. 3 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 12667 records from University of Kentucky Insect Collection. 30457 records from Atlas des Orthoptères et Mantides de France métropolitaine. 23 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 43 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bourdin Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 11 records from Projet d'extension de la carrière de Le Blanc, Queyrac - Données brutes de biodiversité - Le Blanc, Queyrac. 24 records from Ostracoda abundance of Hole 48-406. 215 records from SILENE-FAUNE-PACA - GEOECOLINK_2017_12_18. 2 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 2 records from Encyocratella olivacea Strand, 1907, a senior synonym of Xenodendrophila gabrieli Gallon, 2003 (Araneae: Theraphosidae: Stromatopelminae) with a description of the male. 813 records from UTEP Herpetology Osteology (Arctos). 16 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 154747 records from The Scottish Squirrel Database. 3870 records from Carrière calcaire de Chateaupanne (Mauges-sur-Loire) - modification des conditions d'exploitation - renouvellement de l’autorisation - inventaires 2004-2014 pour étude d'impact carrière. 3 records from Two axiidean ghost shrimps (Crustacea: Decapoda) from India, Guyanacaris keralam sp. nov. (Axiidae) and Paragourretia galathea (K. Sakai, 2017) (Ctenochelidae). 68 records from Planktic foraminifera counts of sediment core V26-124. 168 records from Caracterrización florística del humedal La Abuelita, Municipio de Guapi-Cauca, 2018. 36 records from Selz (Ingelheim am Rhein). 105 records from Expertise batrachologique de la lande de Puycheny la Rouseille par le GMHL en 2013 - Inventaire des données batrachologique. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 14 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 301 records from FBIP: Baboon spider distribution records from selected South African museums. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 1008 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 1432 records from Royal Ontario Museum Fungarium (TRTC). 1759 records from SILENE-FAUNE-PACA - Butterfly_conservation_2017_12_18. 1 records from A new species of Dixonius (Squamata: Gekkonidae) from Vientiane Capital, Laos. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 118478 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 8 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 18938 records from Données bibliographiques et opportunistes Odonates (GON) - Données bibliographiques et opportunistes Odonates issues du SIRF. 1706 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from Düne am Ulvenberg (Darmstadt). 7 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Céline DELTORT. 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 11745 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Chauves-souris - Points d'écoute au sol. 101 records from HRC CRC Small Vessel-Based Monitoring Surveys October-November 2011. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 912 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 1 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 86 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 113 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faunistique de l'ENS des Parc des berges de Seine. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6 records from Novedades taxonómicas en Campanulaceae neotropicales I: dos nuevas especies de Centropogon C. Presl de Venezuela. 3796 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 116 records from Coccoliths in sediment core GIK23065-3. 37 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 13 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 195 records from Abundance and habitat of echinoderms collected during the Bangor-Watamu Expedition in 1969. 90 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 1 records from Plan de gestion 2015 - 2020 du site du site des zones humides du Mondarrain et de l'Artzamendi (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 4307 records from Biomass and mortmass of woody vegetation in metal-contaminated areas (Southern Urals, Russia). 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 204 records from Happywhale - Leopard seal in South Atlantic Ocean. 24 records from Analyses of the recent components of sediment core PS1219-1. 24 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Reptiles. 2 records from Transfer of Homalonychus raghavai Patel & Reddy, 1991 to Storenomorpha Simon 1884 (Araneae: Zodariidae). 374 records from HBRG Invasive Non-native Plants Dataset. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 79106 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 34 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 8154 records from Birds Specimens. 305 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 53 records from Planktic foraminifera abundance of Hole 23-227. 13627 records from DMNS Mammal Collection (Arctos). 133 records from Ecomorphology of the mangrove oyster Crassostrea cucullata in a mangrove swamp in Gazi (Kenya) in May 1991. 52 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivi Pics 2012 - Site Natura 2000 des Barthes de l'Adour. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 170 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 13 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1560 records from Pacific turtle tracks: Turtle-Safe Seas Project. 41 records from Survey of Trogolaphysa Mills (Collembola, Paronellidae) of the Brazilian Amazon including five new species and the description of the dorsal chaetotaxy of the first instar. 32 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from Breynia pseudorostrata (Phyllanthaceae), a new species from Yunnan, Southwest China. 75 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 56 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 11437 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 240 records from Knechtweide (Kohlfurth). 2332 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 797 records from DOSSIER DE DEMANDE DE RENOUVELLEMENT D’AUTORISATION D’EXPLOITATION DE CARRIERE, Communes de Saint-Andéol-le-Château et Givors (69) - Flore St Andéol-1. 85 records from MCP-Mamiferos - Coleção de Mamíferos. 448 records from Benthic macrofauna abundance of sediment core 12930-073. 124 records from Stable isotope data and sedimentology of core SO42-74KL. 82 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 495 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1735 records from Occurrence database of native plants and animals of south-central Chile. 83 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Parc naturel régional de Lorraine. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 4 records from Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China. 510 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 22 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2017 records from Helmintos parásitos de peces del sureste de México. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Olivier LE GALL. 1654 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 37 records from Happywhale - Killer Whale in Arctic Ocean. 950 records from Total foraminifera counts of multinet M21/4_MSN706. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 51 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 111 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Hubert GUIMIER. 1091 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection Rousset -1947-2013. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 3 records from Aristolochia luudamcui (Aristolochiaceae), a new species from northern Vietnam. 76 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 546 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 12094 records from Amino acid addition experiment Metagenome. 71 records from Plan de gestion des Marais du Conseiller - Inventaire et suivi Rhopalocères – Protocole PROPAGE. 2339 records from Données DREAL Centre-Val de Loire - Faune - 2018. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 40263 records from A dataset of bird inventory records at Cloudbridge Nature Reserve, Talamanca Mountains, Costa Rica, between March 2016 and May 2020.. 912 records from Total foraminifera counts from M35/1_MSN1061. 231 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 78192 records from natagora-earlybirds. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 8927 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 11 records from Reptiles Specimens of Akita Prefectural Museum. 168 records from UWIZM Snakes. 44 records from W.E.B. Parc éolien des vents du Serein - Insectes - Inventaire non standardisé. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 1593 records from The Lichen Flora of Serra de São Mamede Natural Park. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 2 records from Two new species of Bucculatrix Zeller from southeast China (Lepidoptera: Bucculatricidae). 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 93 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude écologique du Parc des Lilas (94). 304 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données bibliographiques AsFrA. 27 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaires "Espaces Naturels Sensibles" du Luy (Saugnac-et-Cambran). 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 16 records from Réserves Naturelles de France (RNF) - RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 68 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 9 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de Moliets, la Prade et Moïsan’ (FR7200717) - Inventaire et regroupement de données Natura 2000. 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 4 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent DUPRAT. 10 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 127 records from Planktic foraminifera abundance of Hole 37-332. 521 records from Schanzenanlage Bergham. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 2 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 1140 records from Total foraminifera counts of multinet POS231/3_MSN1332. 160 records from AVJNF: Søholt Storskov, amphibian survey. 3604 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 101 records from Taxonomic study of the genus Tenupalpa Lee et Li, 2021 (Lepidoptera: Gelechiidae Thiotrichinae) from China, with descriptions of fifteen new species. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 154 records from Viabilidad de semillas dispersadas por fauna en la microcuenca Teusacá, Bogotá D.C.. 1 records from Acropoma profundum, a New Species of Lanternbelly (Teleostei: Perciformes: Acropomatidae) from the Solomon Islands. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 5061 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 180 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1823 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 6163 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 446 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Béatrice DELEPINE. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 102 records from Atlantic Forestry Centre Insect Reference Collection. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 130 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 364 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 1044 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 448 records from Benthic macrofauna abundance of sediment core 12930-048. 1140 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 912 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1338 records from Kallisti Limnes subsea pools Metagenome Study. 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 55 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 15124 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 23001 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 35 records from Plan de gestion 2013 - 2018 du site des Coteaux de Las Hies (64) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 584 records from Données transmises au PNR Périgord-Limousin n'étant pas commanditées par le parc - Inventaire Lépidoptères réalisé par David Moore sur le plateau d'Argentine. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 6552 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 136 records from Relative abundance of ostracods in sediment core Sv09. 904 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 273 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 60965 records from SILENE-FAUNE-PACA - Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Mollusques continentaux de France - Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 9 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 4142 records from Trondheim urban biodyversity survey. 93 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 280 records from Size of planktic foraminifera at CTD station PS55/083-1. 315 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 40562 records from R. L. McGregor Herbarium Lichen Collectio
Keywords: GBIF; biodiversity; species occurrences